POSISI PEREMPUAN DALAM NOVEL MARYAM KARYA OKKY MADASARI DAN ANTOLOGI CERPEN AKAR PULE KARYA OKA RUSMINI - VARATISHA ANJANI ABDULLAH; NOVI SRI PURWANINGSIH (Jurnal Dakwah Tabligh, 2018)
This research is a response  the idea of women's emancipation in literary works undergoing a change since it was spearheaded by Kartini. The change in the idea of women's emancipation in the last decade (2000-2017) is a very crucial issue to respond to. This is because the idea of emancipation triggered by female authors offers a solution for women to balance themselves with men in accordance with the problems that currently appear in a very complex and diverse manner. Therefore, this research can be categorized as an effort to deal with humanitarian issues, especially for women who continue to be in a minor position to be able to be equal to men according to the principle of justice. Since its emergence, the authors of modern Indonesian literary works have apparently tried to express ideas about women's struggles. Literary works by the Balai Pustaka published in the 1920s have tried to uncover injustices against women because of their customs. While the literary works published around the 1930s and 1990s continued the idea by explaining the potential and capabilities of women both in public and domestic spaces. This shows that there has been a massive response to gender injustice. The female authors are shown to be strong in voicing women's rights, equality values, and other forms of injustice that they still experience. Interestingly, they expressed the idea of equality and emancipation in accordance with the actual and typical problems of each area such as women's issues at the local level relating to cultural customs and norms, women's problems at the urban level that were individualistic and affected by globalization, especially western culture baratan, up to the problems of women who are shackled by fundamentalist religious values.